Pengembangan Model Peningkatan Kompetensi Pekerja Domestik Indonesia di Malaysia - Ananda, Muna Siva; Sukmawati, Anggraini; Syamsun, Muhammad; Ali, Noor Azman (Jurnal Manajemen Teknologi, 2016)
Abstrak. Masyarakat Ekonomi ASEAN merupakan suatu bentuk integrasi dalam sistem perdagangan bebas di seluruh Negara ASEAN. Indonesia sebagai anggota dari ASEAN memiliki peran yang cukup bersaing diantara Negara lainnya, akan tetapi salah satu persoalan yang dihadapi adalah permasalahan rendahnya tingkat daya saing. Pekerja domestik tidak terampil dari Indonesia menjadi latar belakang permasalahan komunikasi, kekerasan dan banyak kriminalitas lainnya di Malaysia. Faktanya, penempatan pekerja domestik Indonesia di Luar Negeri merupakan solusi terbaik dari pemerintah untuk mengatasi masalah pengangguran. Penelitian ini bertujuan untuk mengetahui permasalahan problematis dan menciptakan suatu model pengembangan untuk peningkatan kompetensi pekerja domestik Indonesia di Malaysia. Data akan dianalisis menggunakan metode Rich Picture dan The House Model. Hasil menunjukkan bahwa untuk membuat perencanaan visi dalam jangka waktu lima tahun ke depan, maka sangat diperlukan peningkatan relevansi wewenang pemerintah pusat, memperbaiki reputasi individu pekerja domestik dan bekerja sama antara pemerintah dengan agensi tenaga kerja. Hasil penelitian ini dapat menjadi implikasi bagi pemerintah maupun lembaga lainnya yang terkait dalam pelaksanaan model Pelatihan Berbasis Kompetensi (PBK). Pemerintah juga dapat menjadikan penelitian ini sebagai referensi dalam pengembangan Pelatihan Berbasis Kompetensi (PBK) kepada pekerja domestik Indonesia dengan adil dan efektif untuk meningkatkan strategi daya saingnya.Kata Kunci: Kompetensi, Pekerja Domestik Indonesia, Pelatihan, Rich Picture, The House ModelÂ Abstract. ASEAN Economic Community is an ASEAN Economic Integration in free trade system all around ASEAN. Indonesia as one of ASEAN Country has a role to compete with other countries, but one of the problems is competitiveness issues. Unskilled domestic workers from Indonesia being the background of miscommunication, workers abuse and many criminality problems in Malaysia. But in fact, placing Indonesian domestic workers in other countries is the best solution to unemployment issues in Indonesia. This study aimed to analyze the problematic situations and create a model that may affect the competency strategies to increase the competitiveness of Indonesian domestic workers in Malaysia. Data from the experts was analyzed using Rich Picture and The House Model. The result showed that in planning the vision for five years term is needed to Enhancing the relevant Governmental Authorities, Establishing the individual reputation and Collaborating between Government and agencies involved. This strategies had been formulated to increase the human resource competencies with Competency-Based Training (CBT). Training and development conducted in Indonesia before placement in abroad is the ways to build workers' quality and then could compete with domestic workers from the Philippines and other countries in Malaysia. The research findings are expected to have implications on government and institutions in the process competency based training models. The government was expected to make the findings as a reference for the Competency-Based Training (CBT) to Indonesian domestic workers fairly and effectively to support its competitiveness strategies.Keywords: Competency, Indonesian domestic workers, Rich Picture, The House Model, Training